Contextualising immigration policy implementation in Europe. - Jordan, Bill; Stråth, Bo; Triandafyllidou, Anna (Journal of Ethnic & Migration Studies, 2003)
The end of the twentieth and the beginning of the twenty-first century in Europe are marked by processes of social and economic change that seriously affect immigration policy design and implementation. Borders have become more permeable, partly because of the emergence of the European Union as a transnational entity without internal frontiers, but also because business has become transnational, transport has become cheaper and faster, and media communication has increased exponentially, embracing distant peoples into a global flow of information. Labour mobility has intensified and some segments of the industrialised countries' labour markets have become accessible to foreign workers. Southern European countries, traditionally sources of immigrant labour force, have suddenly become host countries despite high rates of unemployment among native workers. The flexibility required by post-industrial forms of labour and the permeability of borders have transformed border controls. These are no longer carried out by guardians at the borders. They instead take place within national territories by administrative employees and welfare officers. Large corporations compete for the best-qualified workers while small firms and households take advantage of undocumented immigrant labour. Daily implementation routines of national administrations further complicate matters, while the pressure mounts for conformity with European directives concerning both immigration control and immigrant integration. This paper discusses the above issues, highlighting the context within which immigration policy implementation in Europe operates today. It points to the complexities of the overall picture as well as of individual country realities which are further analysed in the case studies presented in this special issue of JEMS.